A Century of Historical Experience: Christianity and Modern Chinese Social Policy and Legislation - LIU , Jitong (Journal of Research for Christianity in China (JRCC), 2025)
The Opium War of 1840 opened the curtain on a century of humiliation and suffering for modern China, marking the dawn of its semi-colonial era and reflecting the escalation of Christian and Western imperialist aggression into political, military, legal, and institutionalized dimensions. How to comprehensively, systematically, and historically understand the relationship between Western Christian civilization and Eastern Chinese civilization has become a global hot topic. Research focus has shifted from historical, economic, cultural, social, and military issues to political, legal, diplomatic, and regional conflict issues. This paper pioneers a welfare-society historical approach, employing historical archival materials, literature reviews, content analysis, and historical comparisons. It examines the century-long interaction between Christianity and modern Chinese social policy and legislation through theoretical lenses including social welfare, social needs, social modernization, international relations and civilizational exchange, and civilizational conflict theory. This study divides the over 100-year historical development of modern China from the Opium War of 1840 to 1949 into five distinct historical phases: 1840-1894, 1895-1911, 1912-1927, 1928-1937, 1938–1949. It summarizes the structural characteristics and defining features of each historical phase, establishing a broad and enduring historical backdrop for in-depth analysis. Against this context, it comprehensively and systematically traces Christianity's dissemination and influence on legal scholarship, the spirit of the rule of law, social policy, and social legislation. Crucially, it provides a concise historical overview of the factors shaping Christianity's impact on modern China's social policy and legislation over this century. Second, it attempts a comprehensive, systematic, and historical synthesis of the lessons learned from Christianity's interaction with modern Chinese social policy and legislation, focusing on exploring and distilling the universal objective patterns embedded in this century-long engagement. Finally, the author offers a historical evaluation and theoretical reflection on Christianity's impact on modern Chinese social policy and legislation over the past century.